In Situ Treatment of Refractory Perianal Fistulas in Dogs with Low-Dose Allogeneic Adipose-Derived Mesenchymal Stem Cells - Enciso, Nathaly (2024)
Stem cell therapy in dogs has increased considerably in recent years; however, there are few publications on the treatment of perianal fistulas (PF) in this species. The aim of this open-label clinical trial was to demonstrate the efficacy and safety of a new protocol for the in situ administration of low-dose adipose-derived allogeneic stem cells (ASCs) for the treatment of refractory spontaneous perianal fistula. The methodology consisted of applying one to three doses of 5 × 106 cryopreserved allogeneic ASCs to each fistula. The study was performed in 14 dogs regardless of sex, breed, or age, with a clinical diagnosis of refractory PF. Cells diluted in phosphate-buffered saline were applied to five sites of the PF in an amount of 1 × 106 per application site. Efficacy was determined by the complete closure of the fistula, which was observed in 100% of the cases studied one month after therapy, with a subsequent follow-up of 12 to 48 months after therapy. Furthermore, safety was demonstrated by the absence of local or systemic adverse effects. In conclusion, the protocol used in this work demonstrates the efficacy without adverse effects of the in situ application of low doses of allogeneic ASCs, providing a simple, non-invasive, long-lasting and low-cost therapeutic option.